Antifungal properties of chitosan–cobalt(II) complex and its potential on the suppression of damping‐off in cucumber seedlings. Issue 5 (20th April 2016) - Yu, Xueqing; Jing, Yingjun; Xia, Wenchen
Abstract: Chitosan–cobalt(II) complex (CTS–Co) was prepared by the complexation of chitosan with cobalt(II) ions. Fourier transform infrared spectra showed that the amine and secondary –OH groups of chitosan were involved in the complexation with Co(II) ions. The resultant CTS–Co exhibited slightly lower thermal stability than chitosan according to the thermogravimetric analysis. Compared with chitosan, CTS–Co possessed much stronger in vitro antifungal activity. The minimum inhibitory concentrations of CTS–Co against three pathogenic fungi were 250–500 µg/mL, depending on the fungal species. CTS–Co induced the serious leakage of intracellular constituents, which demonstrates that the disturbance on the integrity of the cell membrane is a possible antifungal action of CTS–Co. Furthermore, CTS–Co treatment reduced significantly the disease incidence of damping‐off in cucumber seedlings, and the relative control effect reached 72.2–74.3% after 21‐day cultivation. Additionally, low molecular weight CTS–Co promoted the growth of cucumber seedlings. Our results suggest that CTS–Co is a possible antifungal agent and has promising potential on the control of pathogenic diseases in crop production. © 2016 Curtin University of Technology and John Wiley & Sons, Ltd.